The COVID‐19 Pandemic and Its Influence on Patients With Myotonic Dystrophy Type 1: Lessons Learned - Vera E. A. Kleinveld; Johanna E. Bruijnes; Samuel Labrecque; Danielle E. G. Jeurissen‐Bekkering; Catharina G. Faber; Corinne G. C. Horlings (Brain and Behavior)
ABSTRACT Introduction: Myotonic dystrophy type 1 (DM1) patients might represent a high‐risk population for severe COVID‐19 disease, as cardiopulmonary symptoms are part of the clinical spectrum of DM1. The COVID‐19 pandemic may have impacted DM1 patients. We aimed to determine the effect of the COVID‐19 pandemic on DM1 patients to guide management strategies in possible future pandemics. Methods: Data on the presence of a COVID‐19 infection were retrieved from 195 DM1 patients in the MYODRAFT database. Between August 12 and October 4, 2021, 82 patients and proxies filled out a questionnaire on COVID‐19 symptoms, well‐being, and organization of care. Data were compared to prepandemic data. Results: A total of 18 patients had COVID‐19 (13 confirmed, 5 probable infections). The prevalence of COVID‐19 in our cohort was 9.2%, which was lower than in the Dutch population (11.5%). Four patients (22.2%) were hospitalized due to a COVID‐19 infection, which was higher than in the Dutch population (3.6%). Two infected patients died. A high rate of canceled appointments was reported. Patients reported no change in physical functioning during the pandemic, whereas proxies reported a deterioration in mental and physical well‐being of patients. Conclusions: The prevalence of COVID‐19 infections was not higher in DM1 patients than in the general population, but DM1 patients are more susceptible to complicated disease when infected. Longitudinal data on patient‐reported physical functioning suggest that the COVID‐19 pandemic and the pandemic management strategies implemented did not influence the course of disease in DM1 patients, and similar strategies can be re‐used in comparable situations.